2019
DOI: 10.1021/acsnano.8b08184
|View full text |Cite
|
Sign up to set email alerts
|

Bulk-Like Magnetic Signature of Individual Fe4H Molecular Magnets on Graphene

Abstract: Single-molecule magnets (SMMs) incorporate key properties that make them promising candidates for the emerging field of spintronics. The challenge to realize ordered SMM arrangements on surfaces and at the same time to preserve the magnetic properties upon interaction with the environment is a crucial point on the way to applications. Here we employ inelastic electron tunneling spectroscopy (IETS) to address the magnetic properties in single Fe4 complexes that are adsorbed in a highly ordered arrangement on gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
32
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 32 publications
0
32
0
Order By: Relevance
“…Here, sub-monolayers of Dy 2 @C 80 (CH 2 Ph) molecules were deposited on a graphene/Ir(111) substrate by employing the electrospray deposition (ESD) technique [32][33][34] (see Section 4 for further details). Our STM measurements show that the majority of molecules constitute ordered islands with only small amount of isolated molecules lying on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Here, sub-monolayers of Dy 2 @C 80 (CH 2 Ph) molecules were deposited on a graphene/Ir(111) substrate by employing the electrospray deposition (ESD) technique [32][33][34] (see Section 4 for further details). Our STM measurements show that the majority of molecules constitute ordered islands with only small amount of isolated molecules lying on the surface.…”
Section: Resultsmentioning
confidence: 99%
“…Carefully adjusting tunneling and tip-approach parameters we previously performed IETS measurements on a large number of molecules to obtain reliable statistics, giving the possibility to quantitatively evaluate the impact of the magnetic field [78]. At the same time this procedure captures the variation of step energies that are present within the submonolayer.…”
Section: Fe4h On Graphene/ir(111)mentioning
confidence: 99%
“…above the boiling point of liquid nitrogen, and elegant surface studies of some SMMs have demonstrated the singlemolecule origins of the hysteresis. 12 The advances made to date strengthen the motivation for further research into SMMs, particularly the exploration of new synthetic strategies that aim to increase the temperatures at which these materials function. Considerable effort has been invested into maximizing the effective energy barrier to reversal of the magnetization (U eff ) and the magnetic blocking temperature (T B ).…”
Section: Introductionmentioning
confidence: 96%
“…above the boiling point of liquid nitrogen, and elegant surface studies of some SMMs have demonstrated the single-molecule origins of the hysteresis. 12 …”
Section: Introductionmentioning
confidence: 99%